PENGARUH APLIKASI KOMPOS CAMPURAN AMPAS KOPI DAN TEPUNG CANGKANG TELUR TERHADAP KADAR NITROGEN DAN KALSIUM TANAH REGOSOL SERTA PERTUMBUHAN DAN HASIL TANAMAN OKRA (Abelmoschus esculentus L.) - Madyaratri, Raditya Luh; Suntari, Retno (Jurnal Tanah dan Sumberdaya Lahan, 2023)
One of the medicinal plants that are rarely cultivated in Indonesia is okra. This plant has a business opportunity that can bring benefits to farmers. This research aimed to elucidate the effect of a compost mixture of coffee grounds and milled eggshell on nitrogen and calcium contents in a regosol soil and growth and yield of okra plants. Fertilizer treatments tested were: P0 (control), P1 (100% inorganic), P2 (25% compost + 75% inorganic), P3 (50% compost + 50% inorganic ), P4 (75% compost + 25% inorganic), and P5 (100% compost). The results showed that the application of a compost mixture of coffee grounds and eggshell with a dose of 100% compost had a significant effect on increasing soil pH, total N, and Ca compared to control, namely 30,77%, 147,52%, and 643,54%, but did not significantly affect the organic C of the soil. The application of coffee grounds and milled eggshell compost with a dose of 100% significantly affected plant height at 8 WAP and plant stem diameter at 6 WAP. The application of coffee grounds and milled eggshell compost with a dose of 100% significantly increased fresh fruit weight and dry weight of okra plants, respectively 18.27% and 33.33% compared to the control.